The Concept of Political Communication in the Al-Qur’an - Khoiriah (al-Afkar, Journal For Islamic Studies, 2024)
.  This research explores the concept of political communication in the Qur'an and its relevance to the modern context. Through an in-depth analysis of the verses of the Qur'an, the main principles of political communication are found, such as consultation (shura), honesty, justice, openness, and transparency. The principle of consultation emphasizes the importance of open consultation and exchange of views in decision-making, in line with the concept of participatory democracy. The principles of honesty and justice maintain integrity and public trust, while openness and transparency encourage participation and accountability in governance. Although facing challenges in the digital age, these principles remain relevant and can form the basis for effective, ethical political communication that contributes positively to the development of a harmonious and prosperous society.